2010
DOI: 10.1016/j.amepre.2010.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Walk Score™ As a Global Estimate of Neighborhood Walkability

Abstract: Background Walk Score™ has recently been demonstrated as a valid and reliable tool for estimating access to nearby facilities, a critical component of the physical activity environment. It has not yet been determined whether Walk Score relates to other critical components of the physical activity environment including street connectivity, access to public transit, residential density and/or crime. Purpose The aim of this study is to explore the relationship between Walk Score and objective/subjective measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
249
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 348 publications
(265 citation statements)
references
References 13 publications
7
249
1
8
Order By: Relevance
“…These data were accessed from www.walkscore.com in the spring of 2015. According to Duncan et al, (2011), Walk Score® (www.walkscore.com) is a publicly available large-scale method for calculating walkability (Carr et. 2010(Carr et.…”
Section: Methodsmentioning
confidence: 99%
“…These data were accessed from www.walkscore.com in the spring of 2015. According to Duncan et al, (2011), Walk Score® (www.walkscore.com) is a publicly available large-scale method for calculating walkability (Carr et. 2010(Carr et.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, several studies show that Walk Score can be a valid and reliable measure of estimating neighborhood walkability [61,62,[77][78][79]. For instance, Carr, Dunsiger and Marcus [62] evaluated the validity and reliability of Walk Score to identify neighborhood walkability based on GIS objective measurements and perceived assessments in Rhode Island.…”
Section: Measuring Walkable Neighborhoodsmentioning
confidence: 99%
“…Additionally, several studies show that Walk Score can be a valid and reliable measure of estimating neighborhood walkability [61,62,[77][78][79]. For instance, Carr, Dunsiger and Marcus [62] evaluated the validity and reliability of Walk Score to identify neighborhood walkability based on GIS objective measurements and perceived assessments in Rhode Island. By employing the Pearson's correlation test, they showed that there were significant positive relationships between Walk Scores and various neighborhood walkability indicators (street connectivity, residential density, and access to public transit provisions) as well as between Walk Scores and perceived measurements (summed score of various physical activity environment).…”
Section: Measuring Walkable Neighborhoodsmentioning
confidence: 99%
See 2 more Smart Citations